Engineered probiotic cocktail with two cascade metabolic Escherichia coli for the treatment of hyperlysinemia - Geng, Feng; Wu, Mingyu; Yang, Pan; Li, Xueling; Pan, Xiaohong; Wang, Yadi; Lü, Junhong (Frontiers in Microbiology, 2024)
Engineering probiotics have emerged as a potential strategy for the treatment of metabolic diseases. However, due to the exceptional complexity of these metabolic disorders and the intricate relationship between gut microbes, it is difficult to achieve an ideal therapeutic effect in a specific metabolic disorder using only a single engineered strain. In this work, we proposed a probiotic cocktail strategy by engineering two cascade metabolic bacteria to treat hyperlysinemia, an inherited lysine metabolic disorder with loss of α-aminoadipate semialdehyde synthase (AASS) activity.The probiotic bacterial cocktail enables the maintenance of a metabolic cascade with AASS-like functional activity to maintain the blood lysine concentrations and downstream metabolites. In vitro experimental results showed that the cocktail bacteria had a better metabolic capacity and metabolites balance at a ratio of EcNT (pTLS) and EcNT (pK25) of 1:2. Feeding of the cocktail bacteria to the mouse model effectively reduced the concentration of lysine and balanced saccharopine in the plasma of hyperlysinemia-like mice. These findings not only provide a promising strategy of probiotic stains for the treatment of hyperlysinemia but also highlight the potential of engineered cascade cocktails to intervene and even cure other inherited metabolic diseases.